Vehicle growth trends in Universiti Malaysia Pahang Gambang and Pekan campus - Siti Nur Liyana, Sheikh Roslan (2017)
My research is to determine the vehicle growth trends in Universiti Malaysia Pahang Gambang and Pekan Campus. The vehicle growth trends includes the data collection of to assess trends in vehicle sticker registration within Universiti Malaysia Pahang Gambang and Pekan Campus, to assess vehicle circulation by volume counting at the entrance gate within Universiti Malaysia Pahang Gambang and Pekan Campus and evaluate supply and demand for parking in Gambang Campus. Higher intake number of students affects the vehicle growth trends in Universiti Malaysia Pahang.